Synthesis and Antitumor, Antioxidant Effects Studies of N-Ethylpiperazine Substitute Thiourea Ligands and Their Copper(II) Complexes - Karagoz, Zuhal; Genc, Murat; Yilmaz, Engin; Keser, Serhat (Taylor & Francis Inc, 2013)
A series of N-ethylpiperazine substitute thioureas [C6N2H13NHCSNHR], where R=-C3H5 (L (1) ), -C10H7 (L (2) ), and -C7H7 (L (3) ), and their copper (II) complexes have been synthesized. These ligands and complexes have been characterized by elemental analyses, IR, H-1 and C-13-NMR spectra, UV-Vis, magnetic susceptibility, thermogravimetrical analyses, and MALDI-TOF MS. In vitro antitumor activity of ligands and their complexes has been screened toward several tumor cell lines. The effects on these complexes of the growth of L1210 and MCF7 were studied comparatively with that of free ligands. Antioxidant and radical scavenging activities of synthesized compounds were determined by various in vitro assays including 1,1-diphenyl-2-picryl-hydrazyl free radicals (DPPH), 2,2-azino-bis(3-ethylbenzthiazoline-6-sulfonic acid radicals (ABTS+), and ferrous ion (Fe2+) chelating activities. Moreover, these activities were compared to synthetic and standard antioxidant trolox. The results showed that the synthesized compounds had effective antioxidant power.
Keywords: antioxidant; antitumor; spectroscopy; thiourea